ANALYSIS OF THE IMPACT FROM THE IMPLEMENTATION OF THE PROGRAM TO ACCELERATE THE IMPROVEMENT OF IRRIGATION WATER UTILIZATION (P3-TGAI) IN INCREASING THE PERFORMANCE OF TERTIARY IRRIGATION SYSTEMS IN THE WUNO IRRIGATION AREA, SIGI, CENTRAL SULAWESI - William Arrang Sarungallo (Universitas Tadulako, 2023)
Implementation of the Program for Accelerating Improvement of Irrigation Water Utilization (P3-TGAI) is given to water-using farmers to be able to help maximize the performance of existing irrigation systems to be developed even better. The purpose of this study was to analyze the impact of the implementation of the P3-TGAI in the Wuno Irrigation Area on improving the performance of the irrigation system, and how the results of the evaluation of the irrigation system performance index on P3-TGAI implementers in the Wuno Irrigation Area. This type of research is a quantitative descriptive research that explains the relationship between variables by analyzing numerical data. The population in this study were P3A group administrators who carried out the P3-TGAI program in the Wuno Irrigation Area from 2020 – 2021. The data collection technique used in this research was direct field research which consisted of observations, questionnaires, interviews and documentation. From the results of the study it was found that the impact of the implementation of P3-TGAI on improving the performance of the existing tertiary irrigation system showed an average value of 88.55% with a very increased category, and out of a total of 10 P3A groups through the irrigation system performance survey, good performance was obtained. This shows that the implementation of P3-TGAI in the Wuno Irrigation Area has provided an increase in the performance of the tertiary irrigation system.